2011
DOI: 10.1007/8904_2011_85
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Cardiac “Masses” in a Newborn with Infantile Pompe Disease

Abstract: Glycogen storage disease type II (OMIM #232300), or Pompe disease, may present in the newborn period with moderate-to-severe biventricular hypertrophy with or without left ventricular outflow tract obstruction that typically leads to death from cardiorespiratory failure in the first year of life. Glycogen deposition tends to be uniform, and is only occasionally accompanied by patchy areas of fibrosis. Here, we present an infant identified with biventricular hypertrophy and cardiac masses by prenatal ultrasound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…One of the reviewed cases had been found to have cardiac hypertrophy by routine prenatal ultrasonography at 38 weeks. In 2011, Swarr et al reported a case who had an unusual cardiac 'mass' and biventricular hypertrophy identified by prenatal ultrasound at 30 weeks, which was consistent with the diagnosis of infantile Pompe disease by the detection of GAA activity from a blood spot (11). Following the diagnosis of a patient, it may be necessary for the family to undergo genotype testing and have a genetic consultation with professional geneticists.…”
Section: Discussionmentioning
confidence: 91%
“…One of the reviewed cases had been found to have cardiac hypertrophy by routine prenatal ultrasonography at 38 weeks. In 2011, Swarr et al reported a case who had an unusual cardiac 'mass' and biventricular hypertrophy identified by prenatal ultrasound at 30 weeks, which was consistent with the diagnosis of infantile Pompe disease by the detection of GAA activity from a blood spot (11). Following the diagnosis of a patient, it may be necessary for the family to undergo genotype testing and have a genetic consultation with professional geneticists.…”
Section: Discussionmentioning
confidence: 91%
“…5 The present patient was fed via orogastric feeding tube until DOL 57 because of difficulty in sucking and swallowing. 5 In patients with PD during the neonatal period, CK values range from 478 to 4,158 IU/L (2 to 14 times the normal value) 10,[12][13][14][15][16] , AST values range from 93 to 341 IU/L (2 to 8 times the normal value) 10,[12][13][14][15] , ALT values range from 21 to 160 IU/L (from normal to 4 times the normal value) 10,12,13,17 , and LDH values range from 888 to 1,848 IU/L (2 to 4 times the normal value) 10,12,14,17 . In our case, CK value was higher than those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…We use "prenatal diagnosis", "pompe disease", "glycogen storage disease type " and "acid maltase de ciency" as search terms to nd related articles up to february 2022 in Chinese databases (CNKI database, Wanfang database) and PubMed database (build database). A total of 3 English literatures were retrieved, and 5 children with intrauterine onset Pompe disease were reported [5,6,7]. So including the case we reported ,there was 6 cases (Table 1) in all.…”
Section: Literature Review Materialsmentioning
confidence: 99%